Gewerbeparks in Kenya - Instrumente der Industrialisierung und Regionalentwicklung? - Vorlaufer, Karl (ERDKUNDE, 1986)
In 1967 the Government of Kenya established the parastatal Kenya Industrial Estates Ltd. (KIE) as its major instrument in the implementation of the industrialization policy. The main tasks of KIE were to promote the process of industrialization by creating and fostering small-scale industries under African ownership, to generate employment in the manufacturing sector, to reduce Kenya’s dependency on imports of manufactured goods (import substitution), to develop small and medium-sized towns as centres of industrial production, as well as to promote rural industrialization and thereby to reduce the existing spatial disparities. At the outset KIE followed the traditional estates approach: industrial estates were established in the main urban areas; only those new and modern industrial enterprises that had rented their premises provided by KIE on the side of the estates received loans, technical or management assistance. In 1971 KIE inaugurated the rural Industrial Development Programme, which emphasised the importance of the rural artisan-sector and promoted - on the basis of the extension approach - small industrial and cottage industries even when these were located outside the rural Industrial Development Centres which had been established mainly in smaller towns all over Kenya. In spite of substantial financial and technical aid from various foreign countries, the concept of promoting modern industries showed only limited success in the industrial estates located in the medium-sized towns. The low quality or even total lack of entrepreneural potential in regions outside Nairobi - where KIE concentrated more successfully on the promotion of modern small scale industries - is considered to have been the main reason for many failures. Most of the projects promoted by KIE that turned out to be successful in their operations were located in rural areas. Here especially the small handicraft industries enjoy important locational advantages: local inputs, simple technology and a local market protected by its peripheral location. But, in general the results of KIE’s work have been disappointing. Many sheds in the estates are vacant; rent arrears are high; repayment of loans borrowed from KIE is quite low and many industrial units promoted by KIE are more less inoperative for some part of the year. There have been many enterprises under this scheme that had to give up business entirely. The lack of modern management ability appears to be the main reason for these failures. Therefore it would seem to be more promising to concentrate future promotion on small artisan enterprises located in small central places in rural areas.